2022
DOI: 10.1159/000525528
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Cytomegalovirus Awareness and Knowledge among Health Professionals and Pregnant Women: An Action towards Prevention

Abstract: Introduction: Cytomegalovirus (CMV), is a major cause of childhood disabilities and consensus recommendations emphasize the importance of hygienic measures to reduce perinatal infection. Objective: To evaluate the level of awareness about CMV among health professionals and pregnant women. Methods: We submitted a 20-item online survey regarding CMV perinatal infection to all obstetricians and midwives in Catalonia (Spain) and a 7-item lay-version of the questionnaire to 700 pregnant women. Levels of knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…The correlation between awareness and engagement in clinical research as observed in this survey, aligns with ndings reported in studies on other diseases 32,43 . The correlation between CMV awareness and the recency of pregnancy, as seen in this study, is also consistent with the ndings reported by others 22,44 , indicating the success of information campaigns in the US about CMV. Certainly, individuals most concerned about cCMV disease are motivated by the desire to increase their likelihood of having a healthy baby 45 .…”
Section: Discussionsupporting
confidence: 93%
“…The correlation between awareness and engagement in clinical research as observed in this survey, aligns with ndings reported in studies on other diseases 32,43 . The correlation between CMV awareness and the recency of pregnancy, as seen in this study, is also consistent with the ndings reported by others 22,44 , indicating the success of information campaigns in the US about CMV. Certainly, individuals most concerned about cCMV disease are motivated by the desire to increase their likelihood of having a healthy baby 45 .…”
Section: Discussionsupporting
confidence: 93%
“…This is not surprising given that less than 10% of Australian maternity health care professionals routinely discuss CMV with pregnant patients 20 despite national recommendations to do so 21 . Globally, there is wide variation in pregnant women's knowledge regarding CMV, from 22% in USA 22 and Spain 23 to up to 49%–60% in Germany and France, as measured through surveys 24 …”
Section: Discussionmentioning
confidence: 99%
“…national recommendations to do so. 21 Globally, there is wide variation in pregnant women's knowledge regarding CMV, from 22% in USA 22 and Spain 23 to up to 49%-60% in Germany and France, as measured through surveys. 24 While the experience of shock and anxiety is common to other prenatal diagnoses of fetal abnormality, 25 the CMV experience has several distinct features.…”
mentioning
confidence: 99%
“…This highlights the current need and opportunity to educate the community on best practices and on the newborn screening program. Although understanding of CMV infection may be limited, women have a desire for information [ 35 ]. Prior studies have found similar results among women who initially had a low awareness of cCMV infection but, after being informed of its prevalence and risks, expressed support for screening themselves and their newborns [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Driven by recent successes in optimizing newborn screening methodologies for cCMV infection [ 30 ], the Minnesota Department of Health (MDH) recently announced that it would commence universal screening for all newborns for cCMV, beginning in 2023. However, knowledge and awareness of cCMV is low across all communities, racial and ethnic groups, and socioeconomic strata [ 31 34 ], even among women who are healthcare providers [ 35 ]. Implementation of universal cCMV screening will likely include an extensive evaluation of the infected newborn, creating a risk for disparities in care [ 36 ].…”
Section: Introductionmentioning
confidence: 99%